A prospective comparative study of levobupivacaine hydrochloride 0.5% with ropivacaine hydrochloride 0.75% for peri-operative epidural anesthesia in infra- umbilical surgeries - Shreya Putta,; Satyendra Singh Yadav,; Ankita Gupta,; Rachna Gupta, (Asian Journal of Medical Sciences, 2024)
Background: Epidural anesthesia is a neuraxial regional anesthesia used to provide surgical anesthesia, to supplement general anesthesia, and to provide intra and post-operative analgesia. Levobupivacaine and ropivacaine are local anesthetic agents used in an epidural. Aims and Objectives: The aim of this study is to evaluate the onset and duration of sensory and motor block, duration of analgesia, hemodynamics, and adverse effects of levobupivacaine and ropivacaine given epidurally for infra-umbilical surgeries. Materials and Methods: This prospective randomized study was conducted in a total of 142 patients undergoing an infra-umbilical surgery, divided into two groups of 71 patients each. Group L received 15 mL of 0.5% levobupivacaine and Group R received 15 mL of 0.75% of ropivacaine. The onset and duration of sensory and motor blockade, duration of analgesia, hemodynamics, and side effects were assessed. Results: The mean time of onset of sensory and motor block is faster with ropivacaine (P<0.05). The duration of sensory and motor block and analgesia was longer with ropivacaine (P<0.05), whereas the incidence of side effects such as hypotension was more with ropivacaine. Conclusion: Our study concluded that ropivacaine produced a superior quality of epidural block but levobupivacaine had a more stable hemodynamic profile.